Association between different contexts of physical activity and abdominal obesity and excess weight in adolescents. - Priscila Custódio Martins; Tiago Rodrigues de Lima; Diego Augusto Santos Silva (Universidade Estadual Paulista (UNESP), 2018)
Abstract Aim: To investigate the association between different contexts of physical activity (school commuting, participation in Physical Education classes, school recess, physical activity to improve muscular strength / endurance and overall physical activity) with abdominal obesity and excess weight in adolescents. Method: Cross-sectional study with 1,132 adolescents (14-19 years), enrolled in public schools in São José, Brazil. Information regarding the contexts of physical activity was obtained through questionnaires. The anthropometric indicators used to identify excess weight and abdominal obesity were body mass index (BMI) and waist circumference (WC). Binary logistic regression was used to estimate the odds ratio (OR) and 95% confidence interval (95% CI). Results: Adolescents who actively commuted to school for 10 minutes or longer were 36% less likely (OR: 0.64, 95% CI: 0.58 a 0.71) of having abdominal obesity investigated by WC and 25% less likely (OR: 0.75, 95% CI: 0.65 a 0.86) of having excess weight investigated by means of BMI. The other physical activity contexts were not associated with anthropometric indicators. Conclusion: Active commuting to school was associated with lower odds of having abdominal obesity and excess weight in adolescents. Thus, active commuting to school can be an alternative for maintaining adequate levels of body composition.